Estimation of Seismic Response of R/C Frame Structures to Vertical Earthquake Motion Considering Fixed Support and Soil-StructureInteraction (SSI) - Baş, Selçuk; Baş, Selçuk (My University, 2019)
The present study aims to demonstrate the effects of vertical earthquake excitation on reinforced concrete (R/C) frame structuresincorporating the approaches of Soil-Structure-Interaction (SSI) and rigid foundation. Three earthquake time-histories areregarded to properly elucidate this effect. For the linear time-history analysis (LTHA), finite element model (FEM) of a highrise existing R/C structure designed according to Turkish Seismic Code (TSC, 2007) is developed. For the SSI analysis, theDirect Method (DM) is utilized instead of separated FEM (the Substructure Method). The comparative study is carried outbetween the SSI and the fixed support (FS) model under both only horizontal (H) and horizontal+vertical (HV) seismic motions.The difference between only H and H+V load cases on the basis of the considered parameters showed that vertical earthquakemotion was determined not to be effective on the base shear force, and that the SSI model could be recommended to be takeninto account for analysis due to resulting higher change than the FS. Noticeable increase in the overturning moment revealedthat vertical load bearing elements required more bending moment capacity. The percentage increase in the base axial force isresulted as higher under H load than H+V load, which means that vertical seismic motion treats as balancing effect. Such alower change under H+V load case is directly pertinent to damping properties of the soil media. Therefore, the columns andpiers are recommended to be designed against axial force with more safety according to the outcomes from the FS model.
Keywords: İnşaat Mühendisliği; İnşaat ve Yapı Teknolojisi; Jeokimya ve Jeofizik